Sumbangan Sedimen Dart Sub Das Panasen Dan Noongan Terhadap Pendangkalan Danau Tondano Di Sulawesi Utara (Studi Sedimen Sub DAS Tondano Hulu Bagian Selatan) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The objective of this research are : (1) to know sediment contribution from Panasen and Noongan Sub Catchments into Tondano Lake, (2) to know the changes of bed morphology of the Tondano Lake on Panasen and Noongan river mouths. The study was conducted with primary and secondary data. The primary data were current velocity, water river level and discharge, suspended load, bed load, and depth of the lake around the mouth of Panasen and Noongan rivers. The secondary data included rainfall, geology condition, hydrology, soil, land use, erosion and land unit, and bathymetric map of 1995-1996. The total sediment yields were determined by suspended and bed load. Bed loads was calculated by MPM (Meyer-Peter-Muller) and Livesey method. By comparing bathymetric data of 1995,19%, and 2000, the deposition of Tondano Lake could be explained and analysed. The results of the study showed the suspended dischsrge rating curve and sediment discharge rating curve in Pansen and Noongan Rivers from the upstream to downstream is not getting lower. The upstream of the Pansen river has a very high total sediment, which was effected by farming system of the clove cultivation in the upland of the Panasen river. Analysis of bed material shows that the grain size (d50 and d90) is coarse sand to coarse cobble (0,33519,95 mm). There was a difference of the total erosion rate and sediment yield in the river course which affected deposition material along the transportation. The rate of deposition on the lake bed between 1995 to 1996 was not only affected by sediment from the upstream, but also was influenced by longshore processes, which activated erosion and accresion of the lake coast line.